(untitled) (Open Academia: Journal of Scholarly Research, 2025)
In the article, some water structures are studied on a geographical and hydrological basis. In addition, the hydrological aspects and characteristics of these water structures are evaluated. Hydrological indicators and territorial geographical location ar e determined based on historical maps. The use of ponds and cisterns as drinking water is explained.Information is given about the schematic structure of these water structures, i.e., the dome is made of high-quality brick and alabaster, the top is perforated, and there are holes around them that empty into the pond. Their appearance is in the form of a dome made of bricks, on the nether side there are radial ditches that collect water during the rainy season are passed through slits to a well or other underground container. This, in turn, in improving people’s knowledge of water science, the importance of some ancient water structures today and their effective use in the future, scientifically based proposals and recommendations have been developed.In the process of preparing the article, information from historical sources was used widely and effectively